2019
DOI: 10.3389/fphys.2019.00449
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Endurance and Power Training May Facilitate Motor Unit Size Expansion to Compensate for Declining Motor Unit Numbers in Older Age

Abstract: The evidence concerning the effects of exercise in older age on motor unit (MU) numbers, muscle fiber denervation and reinnervation cycles is inconclusive and it remains unknown whether any effects are dependent on the type of exercise undertaken or are localized to highly used muscles. MU characteristics of the vastus lateralis (VL) were assessed using surface and intramuscular electromyography in eighty-five participants, divided into sub groups based on age (young, old) and athletic discipline (control, end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 40 publications
(56 reference statements)
11
56
0
Order By: Relevance
“…The maximal CMAP represents the summation of all action potentials from all muscle fibres within the recording range of the surface electrode after being activated at the same time. Age‐related decreases in CMAP size have been reported for a number of muscles, including the VL (Piasecki et al., , ), tibialis anterior (McNeil, Doherty, Stashuk, & Rice, ; Piasecki et al., ), biceps brachii (Power et al., ) and soleus (Dalton, McNeil, Doherty, & Rice, ), based on comparisons of young and old participants. Although CMAP size invariably decreases with advancing older age, the association between CMAP size and frailty is not simply explained by ageing per se , because it remained significant after adjusting for age.…”
Section: Discussionmentioning
confidence: 99%
“…The maximal CMAP represents the summation of all action potentials from all muscle fibres within the recording range of the surface electrode after being activated at the same time. Age‐related decreases in CMAP size have been reported for a number of muscles, including the VL (Piasecki et al., , ), tibialis anterior (McNeil, Doherty, Stashuk, & Rice, ; Piasecki et al., ), biceps brachii (Power et al., ) and soleus (Dalton, McNeil, Doherty, & Rice, ), based on comparisons of young and old participants. Although CMAP size invariably decreases with advancing older age, the association between CMAP size and frailty is not simply explained by ageing per se , because it remained significant after adjusting for age.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the aging-related reductions in axons in nerves 8 and loss of motor neurons 50 do suggest that motor neuron loss does indeed occur. Electromyographic studies also suggest almost invariably that motor unit loss occurs during aging as well as an increase in individual motor unit sizes in both athletes and non-athletes, 10,[19][20][21]23,66,67 the latter suggestive of reinnervation. The question thus arises how such an apparent discrepancy between our data and the overwhelming evidence for motor unit remodeling during aging can be reconciled.…”
Section: In Contextmentioning
confidence: 99%
“…15,17,18 Some studies reported no aging-related loss of motor units in master athletes 19 or an attenuated loss even in octogenarians, 20,21 while others found that master athletes do suffer similar motor unit loss as seen in non-athletes. 22,23 Several studies interpreted increased motor unit size 10,23 and larger fiber type groups 24,25 as evidence for improved reinnervation in master athletes, but others found smaller motor unit size, suggested to be representative of less collateral reinnervation in master athletes. 26 Thus, the evidence is equivocal as to whether regular physical activity protects against aging-related motor neuron loss and facilitates reinnervation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of motor units has been larger in young power training group compared to young controls but in elder age neither the power nor the endurance training have impacted this parameter The size of motor units has increased by age without significant effect of power or endurance training. In conclusion, the benefit of regular training may be the improvement in motor unit remodeling [49].…”
Section: Effect Of Physical Exercise On the Muscle Itself And The Whomentioning
confidence: 92%